Global dissemination of a single mutation conferring white pericarp in rice - Sweeney, Megan T.; Thomson, Michael J.; Cho, Yong Gu; Park, Yong Jin; Williamson, Scott H.; Bustamante, Carlos D.; McCouch, Susan R. (Public Library of Science, 2007)
Here we report that the change from the red seeds of wild rice to the white seeds of cultivated rice (Oryza sativa) resulted from the strong selective sweep of a single mutation, a frame-shift deletion within the Rc gene that is found in 97.9% of white rice varieties today. A second mutation, also within Rc, is present in less than 3% of white accessions surveyed. Haplotype analysis revealed that the predominant mutation originated in the japonica subspecies and crossed both geographic and sterility barriers to move into the indica subspecies. A little less than one Mb of japonica DNA hitchhiked with the rc allele into most indica varieties, suggesting that other linked domestication alleles may have been transferred from japonica to indica along with white pericarp color. Our finding provides evidence of active cultural exchange among ancient farmers over the course of rice domestication coupled with very strong, positive selection for a single white allele in both subspecies of O. sativa